Study on anti-collision behavior of new precast concrete curb components in a highway tunnel - Li, Changjun; Zou, Junpeng; He, Wenbin; Ding, Xianying; Zheng, Guoping; Zhuang, Yizhou; Wang, Man (Frontiers in Earth Science, 2022)
In order to improve the prefabrication level of highway mountain tunnels, improve the quality of the project and shorten the construction period, a new type of prefabricated concrete curb member was developed based on the actual project. The production process, construction technical points, on-site assembly technology, etc. are expounded. At the same time, the calculation method for the anti-collision performance of the curb components is proposed, that is, the collision force of 850 kN is calculated by the pseudo-static method, and then the finite element simulation analysis is used to obtain the stress of concrete structure and reinforcement. The results show that the reinforcement will not fail, which can ensure that the curb member will not undergo brittle fracture. This paper aims to provide reference for improving the prefabrication level of highway tunnels.